2004
DOI: 10.1023/b:eare.0000017653.15107.0f
|View full text |Cite
|
Sign up to set email alerts
|

Structural Adjustment Programme, Deforestation and Biodiversity Loss in Ghana

Abstract: Abstract. An empirical investigation is undertaken into the impact of the Structural Adjustment Programme (SAP) on forest and biodiversity loss in Ghana between the period 1965-1995. In the first part of the analysis, a four-equation recursive model, consisting of forest loss, cocoa land, maize land and timber production equations, is employed to examine the impact of the SAP on forest loss. The first equation is a function of the last three, and the last three are functions of mainly prices. Piecewise linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Other studies found evidence that other macroeconomic factors are correlated to deforestation. They encompass the role of real exchange rates (Arcand et al, 2008), agricultural activity (Barbier, 2004), access to capital, public policies (Benhin and Barbier, 2004;Combes-Motel et al, 2009), population (Cropper and Griffiths, 1994) or timber harvesting (Damette and Delacote, 2011). Heilmayr, (2014) investigates the impact of plantations on natural forests: plantation expansion is negatively correlated to natural forests dedicated to forest product extraction, and positively related to unharvested natural forests and the associated generation of ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found evidence that other macroeconomic factors are correlated to deforestation. They encompass the role of real exchange rates (Arcand et al, 2008), agricultural activity (Barbier, 2004), access to capital, public policies (Benhin and Barbier, 2004;Combes-Motel et al, 2009), population (Cropper and Griffiths, 1994) or timber harvesting (Damette and Delacote, 2011). Heilmayr, (2014) investigates the impact of plantations on natural forests: plantation expansion is negatively correlated to natural forests dedicated to forest product extraction, and positively related to unharvested natural forests and the associated generation of ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is estimated that more than 75% of the protein in West Africa comes from bush meat (Asibey, 1974;Benhin and Barbier, 2004). The bush meat trade supports about 300,000 people in rural areas, out of which 270,000 are self-employed hunters.…”
Section: Gold Mining and Deforestation In Ghanamentioning
confidence: 99%
“…In addition, 70% of Ghanaians depend only on traditional medicine for health care. Traditional medicines are derived from roughly 2000 plants (Zhang, 2001) which are also exported to Europe for the production of medicine (Benhin and Barbier, 2004). Furthermore, many forest products are used as raw materials in household and local production of baskets, furniture, roofing materials, musical instruments, jewelry, hunting tools, traditional drums, and other items.…”
Section: Gold Mining and Deforestation In Ghanamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the direct causes of deforestation and forest degradation are clearing of forests for food and cash crop farming, logging (both legal and illegal), fuelwood harvesting, infrastructure expansion, and wild fires. The underlying causes are a high international demand for timber, cocoa and minerals, poverty, corruption, the overcapacity of the forest industry, low forest fees, the low enforcement of forestry rules, population growth, urbanization and land and tree tenure issues (Appiah et al 2009, Benhin and Barbier 2004, Hansen et al 2009). …”
Section: Tropical Deforestation and Forest Degradationmentioning
confidence: 99%